2015
DOI: 10.1016/j.bbadis.2015.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori chronic infection and mucosal inflammation switches the human gastric glycosylation pathways

Abstract: Helicobacter pylori exploits host glycoconjugates to colonize the gastric niche. Infection can persist for decades promoting chronic inflammation, and in a subset of individuals lesions can silently progress to cancer. This study shows that H. pylori chronic infection and gastric tissue inflammation result in a remodeling of the gastric glycophenotype with increased expression of sialyl-Lewis a/x antigens due to transcriptional up-regulation of the B3GNT5, B3GALT5, and FUT3 genes. We observed that H. pylori in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
54
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 68 publications
(61 citation statements)
references
References 61 publications
4
54
2
1
Order By: Relevance
“…In regards to pathogenic infections, it has been previously shown that Helicobacter pylori induces B3GNT5 expression and that the ABO(H)/Lewis blood group antigens expressed in H. pylori - infected individuals act as receptors for BabA, thereby facilitating colonization of the gastric niche33. Likewise, the Shiga toxin from urinary tract infection-causing enterohemorrhagic E. coli was shown to recognize the terminal epitope of P 1 , Galα1-4Galβ1-4 following internalization of the toxin by receptor-mediated endocytosis34.…”
Section: Discussionmentioning
confidence: 99%
“…In regards to pathogenic infections, it has been previously shown that Helicobacter pylori induces B3GNT5 expression and that the ABO(H)/Lewis blood group antigens expressed in H. pylori - infected individuals act as receptors for BabA, thereby facilitating colonization of the gastric niche33. Likewise, the Shiga toxin from urinary tract infection-causing enterohemorrhagic E. coli was shown to recognize the terminal epitope of P 1 , Galα1-4Galβ1-4 following internalization of the toxin by receptor-mediated endocytosis34.…”
Section: Discussionmentioning
confidence: 99%
“…The antigen-binding adhesin BabA binds to fucosylated antigens normally expressed by secretor individuals 212 , and the sialic acid-binding adhesin SabA recognizes sialylated Lewis glycans (sialyl Lewis a (SLe a ) and SLe x ) expressed in gastritis 213 . Inflammation-induced glycosylation alterations, such as the aberrant overexpression of SLe x , occur because of changes in glycosyltransferases expression 59,60,214 . Changes in glycosylation have also been studied in acute-phase proteins, such as α1 antitrypsin, as potential biomarkers in cancer and in acute and chronic inflammatory conditions 215 .…”
Section: Box 3 | Glycosylation At the Interface Of Inflammation-inducmentioning
confidence: 99%
“…The glycan changes are caused by transcriptional up-regulation of the B3GNT5, B3GALT5, and FUT3 genes [73]. …”
Section: Alterations Of Mucin Glycosylation At Diseasementioning
confidence: 99%